On‐vine withering process of 'Moscato bianco' grapes: effect of cane‐cut system on volatile composition. (17th September 2018) - Giacosa, Simone; Giordano, Manuela; Vilanova, Mar; Cagnasso, Enzo; Río Segade, Susana; Rolle, Luca
Abstract: BACKGROUND: Cane‐cut on‐vine withering is a grape dehydration technique used for dry and sweet wine production. The aim of this work was to study the influence of the cane‐cut technique applied at harvest to Moscato bianco grapes during the on‐vine withering process to produce dehydrated berries with a different chemical composition and a volatile profile. RESULTS: After 24 days of dehydration, an on‐vine withering system using the cane‐cut technique induced an increase in the total volatile content compared with grapes produced with a normal on‐vine withering process. This increase was greater in glycosidically bound volatile compounds than in the free fraction. Bound linalool showed a significant increase of 52% when the cane‐cut withering system was applied but the grapes that were normally withered appeared to be less prone to the loss of free linalool. A significant increase in the glycosylated forms of nerol and geraniol was also observed in the two on‐vine withering systems on the 24th day compared with the control (fresh grapes at harvest date). CONCLUSION: A cane‐cut, on‐vine withering system applied at harvest induced changes in the volatile composition of Moscato bianco grapes increasing total volatile content, consisting mainly of bound compounds, by the 24th day of dehydration. The grapes dehydrated on‐vine using this new system also showed significantly greater content of most of the free volatile compounds detected. © 2018 Society of Chemical Industry